JOB PERFORMANCE PEGAWAI BEA CUKAI: PERAN TRANSFORMATIONAL LEADERSHIP, EMOTIONAL INTELLIGENCE DAN JOB SATISFACTION - Saputra , I Putu Evan Diatmika; Muthia, Muthia (JURNAL PERSPEKTIF BEA DAN CUKAI, 2024)
This research aims to examine the effects of transformational leadership, emotional intelligence and job satisfaction on job performance in public sector organizations. It also determines the role of job satisfaction as a mediator of the relationship between transformational leadership and emotional intelligence on job performance. This research was conducted at the Directorate General of Customs and Excise Indonesia (DGCE). Primary data was obtained through questionnaire with a total of 611 respondents from ASN employees in each of DGCE units starting from the head office, vertical offices and technical implementation units. The research hypothesis was tested using partial least squares structural equation model (PLS-SEM). The results of this research show that transformational leadership and emotional intelligence have a significant influence on job performance and job satisfaction. However, job satisfaction does not have a significant influence or mediating role on job performance in DGCE. Keywords : transformational leadership, emotional intelligence, job satisfaction, job performance, public sector organization.